Panel Regression on the impact of Energy Consumption and Trade Openness on Economic Growth in Some Selected Sub-Sahara African Countries - Ahmad Tanko, Nafisatu; M. O, . Adenomon; M. U. , Adehi (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Energy is necessary for a holistic economic system that includes the production, distribution, and consumption of products and services. This suggests that energy access and consumption are either directly or indirectly related to the growth of the majority of developing and growing economies. As a result, energy is essential to the production of goods and services that are either sold elsewhere or consumed locally. Trade openness and energy output are thus two of the most important factors determining a nation's economic health. Thus, this study aimed at examining the impact of energy consumption and trade openness on economic growth in selected Sub-Saharan African (SSA) Countries using panel regression models. The data for the study were collected from World Bank Data Base from 2010 -2022. The data collected were analyzed using Pooled Regression, Fixed Effect (FE) and Random Effect (RE) regression models. The Hausman specification test result revealed that the random effect model is more efficient for modelling the impact of energy consumption and trade openness on economic growth in SSA Countries (Housman specification test statistic = 5.31, p > 0.05). The study revealed further that there is presence of random effect (test statistic = 611. 18, p < 0.05) and there is cross sectional independence (test statistic = 39.455, p < 0.05) in the data. In addition, it was discovered that both energy consumption and trade openness have negative and significant impact on economic growth of selected SSA Countries (-1.7342, p < 0.05;. Based on these findings, it was recommended that policy makers in the selected Countries that should formulated policies that will provide an enabling environment for effective and positive contribution of oil consumption and trade openness to economic growth in Nigeria.